A rapid and sensitive profiling of free fatty acids using liquid chromatography electrospray ionization tandem mass spectrometry (LC/ESI-MS/MS) after chemical derivatization. Issue 38 (30th March 2016) - Mok, Hyuck Jun; Lee, Jae Won; Bandu, Raju; Kang, Hong Seok; Kim, Kyun-Hwan; Kim, Kwang Pyo
Abstract : A mass spectrometry method for the improved identification and quantification of free fatty acids (FFAs) based on derivatization using trimethylsilyldiazomethane (TMSD) was developed and validated to be an sensitive and accurate method for analyzing FFAs. Abstract : Free fatty acids (FFAs) have diverse roles in cellular energy and signaling and they are critical molecules in various biological states. Due to the poor ionization efficiency of FFAs under electrospray ionization mass spectrometry (ESI-MS) conditions, it is a challenging aspect to construct a robust platform for profiling of various FFAs in biological samples using liquid chromatography ESI-MS. In the present study, we applied trimethylsilyldiazomethane (TMSD) derivatization to improve ionization efficiencies in the profiling of FFAs. Multiple reaction monitoring (MRM) was used for the selective quantification of methylated FFAs. The optimal TMSD methylation was validated for a reliable FFA profiling. Furthermore, the high-throughput analysis of FFAs was successfully performed in short analysis and derivatization times. To verify the utility and effectiveness of the developed method, we compared both methylation and nonmethylation (intact FFA) data in the profiling of FFAs in mice liver and plasma. It is noteworthy that the methylation derivatization provided better results in FFA profiling. Further, we performed statistical data analysis where HBV and mock mice tissues were discriminated when the methylated FFAs data were used. In the lipidomics field, the present method can also be applied for the profiling of FFAs in biological samples for biomarker discovery. The present validated LC/ESI-MS/MS assay method may also be used for FFA profiling modeling studies in other biomedical samples.